The tyrant's writ : myths and images of writing in ancient Greece - Steiner, Deborah, 1960- (Princeton legacy library., 1994)
Covering material as diverse as curse tablets, coins, tattoos, and legal decrees, Deborah Steiner explores the reception of writing in archaic and classical Greece. She moves beyond questions concerning ancient literacy and the origins of the Greek alphabet to examine representations of writing in the myths and imaginative literature of the period. Maintaining that the Greek alphabet was not seen purely as a means of transcribing and preserving the spoken word, the author investigates parallels between writing and other signifiers, such as omens, tokens, and talismans; the role of inscription in religious rites, including cursing, oath-taking, and dedication; and perceptions of how writing functioned both in autocracies and democracies.